2013
DOI: 10.1021/jf403647u
|View full text |Cite
|
Sign up to set email alerts
|

Pyrrolizidine Alkaloids in the Food Chain: Development, Validation, and Application of a New HPLC-ESI-MS/MS Sum Parameter Method

Abstract: Contamination of food and feed with pyrrolizidine alkaloids is currently discussed as a potential health risk. Here, we report the development of a new HPLC-ESI-MS/MS sum parameter method to quantitate the pyrrolizidine alkaloid content in complex food matrices. The procedure was validated for honey and culinary herbs. Isotopically labeled 7-O-9-O-dibutyroyl-[9,9-(2)H2]-retronecine was synthesized and utilized as an internal standard for validation and quantitation. The total pyrrolizidine alkaloid content of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
34
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 60 publications
(35 citation statements)
references
References 19 publications
1
34
0
Order By: Relevance
“…The elution was relatively fast and possible to carry out without the use of back pressure. Cramer et al, 2013 eliminated the N-oxide zinc reduction step by increasing the amount of LiAlH 4 and also decreased the time of refrigeration and confirmed the efficiency of reduction of PAs to the backbone structure experimentally. However, it was observed that the zinc reduction step reduces the viscosity of the honey extract.…”
Section: Methods Development and Optimizationsupporting
confidence: 61%
See 2 more Smart Citations
“…The elution was relatively fast and possible to carry out without the use of back pressure. Cramer et al, 2013 eliminated the N-oxide zinc reduction step by increasing the amount of LiAlH 4 and also decreased the time of refrigeration and confirmed the efficiency of reduction of PAs to the backbone structure experimentally. However, it was observed that the zinc reduction step reduces the viscosity of the honey extract.…”
Section: Methods Development and Optimizationsupporting
confidence: 61%
“…1) and expressed as single sum parameter value. The advantages and disadvantages of the sum parameter method have been already described in details (Kempf et al 2008;Cramer et al 2013;Kowalczyk and Kwiatek 2017).…”
Section: Methods Development and Optimizationmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, contaminations with PAs could be detected, among other product groups, in herb products. Next to herbal teas and herbal food supplements they were also detected in culinary herb mixes (Cramer, Schiebel, Ernst, & Beuerle, 2013). The star anise, also called Chinese star anise (derived from Illicium verum) is used as culinary spice and for herbal teas.…”
Section: Endogenous Compounds and Contaminations With Toxic Plant Commentioning
confidence: 99%
“…In addition to GC/MS, HPTLC (13) and ELISA (14) methods that have been lately reported for the qualitative detection of PAs, LC/MS is among the main methods used for qualitative and quantitative analysis (15)(16)(17). In LC/MS protocols, N-oxides are usually reduced and consequently selectively retained by strong cation exchange (SCX) SPE cartridges, from which they are eluted with ammoniated methanol (17)(18)(19).…”
mentioning
confidence: 99%